Development of a Natural and Social Sciences Learning Model Based on Socio Scientific Issues to Strengthen Scientific Literacy of Islamic Elementary School Students - Anatri Desstya; Ika Candra Sayekti; Fitri Puji Rahmawati; Yulia Maftuhah Hidayati; Honest Ummi Kaltsum; Yogi Muthohir Zuhad Mahya; Shafa Joyce Putri Kamila; Nur Ahlul Khotimah; Nita Fidyastuti; Alfina Mutiara Diaz (Postgraduate, University of Mataram, 2024)
Science learning in the independent curriculum seems to still stand alone, is oriented cognitive learning outcomes, does not relate to social issues, and is not yet oriented towards scientific literacy. In the field, there is no yet available natural and social science learning model framework that structurally involved social, ethical and moral issues, through a Socio Scientific Issues (SSI) approach that is applicable to educational practitioners. This research aims to produce a framework for a natural and social science (IPAS) learning model based on Socio Scientific Issues (SSI) approach to strengthen students' scientific literacy in elementary school. This Design Based Research (DBR) was carried out through stages problem identification and analysis; design; testing and evaluation); and reflection. This research involved teachers and students of grade IV Islamic elementary schools in Kartasura, Sukoharjo, were taken using purposive sampling. The model validity test was carried out by experts in the fields of learning models, content and language. The resulting IPAS learning model based on Socio Scientific Issues (SSI) approach framework has a validity of 99.2% (very valid) and a learning tool of 96.5% (very valid). This model is very practical to implement (score 86%), and is quite effective in strengthening the scientific literacy of elementary school students. This model is suitable for application at other elementary school levels in a wider scope, with careful planning in terms of infrastructure and time management.